Differences in the prevalence of physical activity and cardiovascular risk factors between people living at low (<1,001 m) compared to moderate (1,001-2,000 m) altitude - Martin Burtscher; Grégoire P Millet; Jeannette Klimont; Johannes Burtscher (AIMS Press, 2021)
Living at moderate altitude (up to about 2,000 m) was shown to be associated with distinct health benefits, including lower mortality from cardiovascular diseases and certain cancers. However, it remains unclear, whether those benefits are mainly due to environmental conditions (e.g., hypoxia, temperature, solar ultra-violet radiation) or differences in lifestyle behavior, including regular physical activity levels. This study aims to compare altitude-related differences in levels of physical activity and the prevalence of cardiovascular risk factors such as obesity, hypertension, hypercholesterolemia, and diabetes in an Alpine country. We interrogated the Austrian Health Interview Survey (ATHIS) 2019, a nationally representative study of persons aged over 15 years living in private Austrian households. The results confirm a higher prevalence of hypertension (24.2% vs. 16.8%) in men living at low (<1,001 m) compared to those at moderate (1,001 to 2,000 m) altitude. Women living above 1,000 m tend to have a lower prevalence of hypercholesterolemia (14.8% vs. 18.8%) and diabetes (3.2% vs. 5.6%) than their lower living peers. Both sexes have lower average body mass index (BMI) when residing at moderate altitude (men: 25.7, women: 23.9) compared to those living lower (26.6 and 25.2). Severe obesity (BMI > 40) is almost exclusively restricted to low altitude dwellers. Only men report to be more physically active on average when living higher (1,453 vs. 1,113 weekly MET minutes). These novel findings confirm some distinct benefits of moderate altitude residence on heath. Beside climate conditions, differences in lifestyle behavior, i.e., physical activity, have to be considered when interpreting those health-related divergences, and consequently also mortality data, between people residing at low and moderate altitudes.